2019
DOI: 10.1017/s1368980018003798
|View full text |Cite
|
Sign up to set email alerts
|

Neighbour home gardening predicts dietary diversity among rural Tanzanian women

Abstract: ObjectiveThe present study’s aim was to assess the impact of a nutrition-sensitive intervention on dietary diversity and home gardening among non-participants residing within intervention communities.DesignThe study was a cross-sectional risk factor analysis using linear and logistic multivariate models.SettingIn Tanzania, women and children often consume monotonous diets of poor nutritional value primarily because of physical or financial inaccessibility or low awareness of healthy foods.ParticipantsParticipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…The consumption of a monotonous diet may deprive the adequate intake of essential vitamins and minerals, which can affect the nutritional status of children [49]. This finding concurs with the study conducted in Tanzania by Blakstad et al [129], who found that children and women who consumed a monotonous diet were malnourished compared to those who consumed a diverse food diet. Similarly, Shakya [130] showed that children who mainly consumed monotonous food, comprised primarily of carbohydrates, were nutritionally deprived.…”
Section: Consumption Of a Monotonous Dietsupporting
confidence: 89%
“…The consumption of a monotonous diet may deprive the adequate intake of essential vitamins and minerals, which can affect the nutritional status of children [49]. This finding concurs with the study conducted in Tanzania by Blakstad et al [129], who found that children and women who consumed a monotonous diet were malnourished compared to those who consumed a diverse food diet. Similarly, Shakya [130] showed that children who mainly consumed monotonous food, comprised primarily of carbohydrates, were nutritionally deprived.…”
Section: Consumption Of a Monotonous Dietsupporting
confidence: 89%
“…Monotonous food consumption can reduce the adequacy of essential vitamins and minerals, which can affect children's nutritional status (Zhou et al, 2020). This finding is in line with a study conducted in Tanzania by Blakstad et al (Blakstad et al, 2019), who found that children and women who eat monotonous meals experience malnutrition compared to those who eat variable foods Shakya (Pritika, 2017) also shows that most children who eat meals monotonously , especially those containing carbohydrates, suffer from malnutrition. Therefore, malnutrition caused by monotonous food consumption can lead to malnutrition in children.…”
Section: Discussionsupporting
confidence: 70%
“…Additionally, our previous research found positive associations between the gardening activities of one household and the dietary diversity of neighbouring households, suggesting that there may be positive externalities of the intervention to the larger community, and not just the beneficiary households. Specifically, women who lived near a neighbour who grew crops in a home garden had 0.53 higher dietary diversity score (consumed 0.53 more food groups per day, on average) and had 2.77 times the odds of achieving minimum dietary diversity compared with those who did not (Blakstad et al, 2019). The magnitude of impact on neighbours' dietary diversity is of similar magnitude as the effect size of INT on study participants' dietary diversity (0.50 food groups).…”
Section: Discussionmentioning
confidence: 99%